B431 Lateral erector spinae plane block for lengthening of growing spinal rods after previous spinal instrumentation in children. Case series. (11th August 2022) - Mislovic, B; Hassan, M
Abstract : Background and Aims: Ultrasound guided erector spinae plane block (ESPB) is very effective means of pain relief for spinal surgeries. Some pediatric patients need their spinal surgeries at earlier age, and due to further growth, they need various additional procedures, most often, lengthening of metal rods. These instrumentations make the visualization of a transversus process very difficult or impossible. Since June 2019 we have been using more lateral approach for this successful nerve blockade, where we used a rib as a landmark structure instead of transversus process. We have called this block Lateral ESPB(LESPB). Methods: After approval from the local ethical committee, we identified medical records of patients who received LESPB since June 2019. On one side we performed Lateral ESPB and we injected local anaesthetic more laterally where shadow of the rib could be seen. On contralateral side, where transversus process could be visible we proceed with conventional ESPB. Results: We found 6 patients who fulfilled our criteria. Pain scores in recovery 1 and 6 hours after a surgery were 0 except one patient who had pains score 5, 1 hour after surgery, but no intervention was needed. No opioids were used in first 6 hours in any patient and 3 out of 6 patients (50%) received no opiods postoperatively. Conclusions: From our very limited experience we can conclude that Lateral ESPB is valuable block which can provide significant pain relief post spinal instrumentation where transversus process cannot be visualised by ultrasound.